PTH-046 ERCP – should we stent the pancreatic duct after guidewire cannulation of the pancreas?. (June 2019) - Napier, Duncan; Masterman, Benjamin; Kokrashvili, Alex; Colleypriest, Ben
Abstract : Introduction: Post ERCP pancreatitis (PEP) is a serious complication of ERCP. 1 Procedural risk factors include pancreatic duct injection of contrast and pancreatic guidewire cannulation. Common bile duct (CBD) access can be challenging and pancreatic guidewire assisted cannulation (PGWAC) is an accepted technique to facilitate this. Rectal non-steroidal anti-inflammatory (NSAID) administration is now widely adopted to minimise PEP in all ERCPs, whilst additional pancreatic stenting is recommended in high risk cases 1, albeit with limited evidence. Methods: Retrospective data was collected from the local endoscopy database identifying all patients undergoing ERCP within 3 years. Every ERCP report was reviewed; indication, diagnosis, use of rectal NSAID and whether the CBD or pancreatic duct (PD) was cannulated was documented. This data was then cross-referenced with hospital records to identify all patients diagnosed with pancreatitis within one-week of ERCP by reviewing medical records, biochemistry and imaging. Results: 813 ERCPs were performed in the study period; 7 were subsequently excluded due to insufficient data. The commonest indication for ERCP was choledocholithiasis (65.9%). CBD cannulation rates were 93.56%. Overall PEP rate was 2.85% (95% CI, 1.82–4.25). The ampulla was not reached in 22 cases and thus excluded (risk of PEP deemed very low). Of the remaining 784 patients, 107 had inadvertent PD cannulation. When the PD was cannulated, the CBD was successfully cannulated in 96.3% using PGWAC, whereas when the PD was not cannulated, cannulation rate was 92.3%. However in the cohort who had PD cannulation, PEP rates were statistically significantly higher 14.02% compared to those that did not have PD cannulation (1.18%) p<0.05. PEP rates were 12.75% in successful PGWAC, 40% in unsuccessful PGWAC, 1.23% in successful CBD cannulation without PGWAC and 0% in unsuccessful CBD cannulation without PGWAC. Conclusions: PGWAC is an accepted technique to facilitate difficult CBD access. In the era of NSAID PEP prophylaxis for all patients the place of pancreatic stents is uncertain. Current practice for stenting the PD after PGWAC is variable. Our data would suggest that PGWAC immediately puts the patient into a high risk group for PEP and pancreatic stenting should be considered. The risk of PEP in patients where CBD cannulation is successful is 12.75% in PGWAC compared with 1.23% where the PD is not cannulated with a wire. The overall low PEP rates in this study could be potentially decreased if pancreatic stenting was employed after PGWAC and should be a further area for studies. Reference: Dumonceau J-M, Andriulli A, Elmunzer B J, et al. Prophylaxis of post-ERCP pancreatitis: European society of gastrointestinal endoscopy - Updated June 2014. Endoscopy 2014;46:799–815.